Pro-fibrinolytic potential of the third larval stage of Ascaris suum as a possible mechanism facilitating its migration through the host tissues - Alicia Diosdado; Fernando Simón; Rodrigo Morchón; Javier González-Miguel (Parasites & Vectors, 2020)
Abstract Background Ascaris roundworms are the parasitic nematodes responsible for causing human and porcine ascariasis. Whereas A. lumbricoides is the most common soil-transmitted helminth infecting humans in the world, A. suum causes important economic losses in the porcine industry. The latter has been proposed as a model for the study of A. lumbricoides since both species are closely related. The third larval stage of these parasites carries out an intriguing and complex hepatopulmonary route through the bloodstream of its hosts. This allows the interaction between larvae and the physiological mechanisms of the hosts circulatory system, such as the fibrinolytic system. Parasite migration has been widely linked to the activation of this system by pathogens that are able to bind plasminogen and enhance plasmin generation. Therefore, the aim of this study was to examine the interaction between the infective third larval stage of A. suum and the host fibrinolytic system as a model of the host-Ascaris spp. relationships. Methods Infective larvae were obtained after incubating and hatching fertile eggs of A. suum in order to extract their cuticle and excretory/secretory antigens. The ability of both extracts to bind and activate plasminogen, as well as promote plasmin generation were assayed by ELISA and western blot. The location of plasminogen binding on the larval surface was revealed by immunofluorescence. The plasminogen-binding proteins from both antigenic extracts were revealed by two-dimensional electrophoresis and plasminogen-ligand blotting, and identified by mass spectrometry. Results Cuticle and excretory/secretory antigens from infective larvae of A. suum were able to bind plasminogen and promote plasmin generation in the presence of plasminogen activators. Plasminogen binding was located on the larval surface. Twelve plasminogen-binding proteins were identified in both antigenic extracts. Conclusions To the best of our knowledge, the present results showed for the first time, the pro-fibrinolytic potential of infective larvae of Ascaris spp., which suggests a novel parasite survival mechanism by facilitating the migration through host tissues.